Res publica and the Roman republic : 'without body or form' - Hodgson, Louise Lovelace (Oxford University Press, 2017)
'Res Publica and the Roman Republic' explores the political crisis at the end of the Roman Republic through the changing perceptions of the political sphere itself, the res publica. The volume seeks to show how the rhetoric surrounding the latter mirrors the changes in the Roman political landscape throughout this period